(3OYGA LhT GdUZjQs - (3efShH Edi SjOfG Ydj Hf CHj WGdHs
(3ChdgG (B:s
(3GdaUd GdChd Edgj ce ef YOh GfJMi Ydi Sja YOGJg hTMP dj XHI eOjJg hCQga dj THG MOgs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQgEdgj hSjOj hces
(3aj BNQg COYjI hChQGO HGddZI GdYQHjI hGdJQcjI hGdaGQSjI ef b(B9 - (3b(B28s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJUha hGdBOGH GdTQYjIs